ESCALATION OF HUMAN RESOURCE PRODUCTIVITY AND IMPLEMENTATION OF COMPANY SUSTAINABILITY COMMITMENTS IN THE DESIGN OF GOTO HEADQUARTERS - Harits Imaduddin, Haidar
GoTo is a technology company that has recently successfully made an initial public offering. Gojek and Tokopedia, as the main entities of GoTo, have dominated the digital market in Indonesia over the past decade. However, the company faces business challenges and economic uncertainties that have led GoTo to streamline operations by reducing the number of employees by up to 1900 over the past two years. This situation is exacerbated by the company still recording a loss of 7.16 trillion rupiah in the first semester of 2023. Thus, the reduction of employees has a significant impact on the company considering the average salary of GoTo employees is as high as 118.9 million per month. Given the high incentives provided, GoTo needs to ensure its employees have maximum productivity to support GoTo's growth. The existing GoTo office is still in separate office buildings designed by developers, so it does not fully accommodate the needs of employees. On the other hand, GoTo also has a sustainability mission called the "Three Zero Commitment," which includes zero emissions, zero waste, and zero barriers. One of the targets set in this commitment is to transition 100% of GoTo offices to renewable energy and implement zero waste efforts across all GoTo operations. To address these issues, architecture can tackle them with the construction of offices that can improve employee wellbeing and sustainable office buildings. To ensure sustainability aspects, this project will strive to meet BREEAM sustainability rating standards and LEED certification by reducing carbon emissions, using low impact design, adapting to climate change, having ecological value, and protecting biodiversity. The office and surrounding landscape design also need to reduce the impact of pollution and Urban Heat Island, so the building can provide user comfort and be sustainable at the same time. The vision of this office project is to improve the productivity of GoTo employees and facilitate GoTo in achieving its sustainability targets summarized in the "Three Zero Commitment." From this vision, three missions are derived: the office as a facility that improves employee quality of life, the office as a facility that uses 100% renewable energy and has high sustainability value, and the office as a facility for learning and social interaction. The scope of this project design is an office permitted to be built in the city-scale trade and service zone strata 1 (K-1) according to RDTR 2022 regulated in Pergub No 31 of 2022. The K-1 zone is a strata sub-zone 1 with the highest flexibility and intensity of space utilization. This project is the construction of a new office for PT GoTo Gojek Tokopedia Tbk. The main function of this office project is as a facility